CHARACTERISTICS OF SAMPLES IN RUSSIAN-LATVIAN RESEARCH PROJECT ON PEDAGOGUE PROFESSIONAL IDENTITY: ANALYSIS OF PERSONAL INFORMATION ITEMS - Bogdanova, Tatiana; Jermolajeva, Jelena; Silchenkova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The study is a part of Latvian-Russian research project on the professional identity of teacher started in 2013. The aim of the article is to analyze and compare the data of Latvian and Russian respondents in personal information items in two questionnaires for school teachers and university lecturers designed for studying the structural model of teacher’s professional identity. The surveys were carried out in 2015 (for university teachers, 198 respondents) and 2017 (for school teachers, 433 respondents). The common features of the modern pedagogical staff of the two countries are revealed, and differences and problem zones of the educational systems are indicated. Examining respondents’ personal information items, researchers revealed that in both countries, official statistical data on the pedagogical community, especially on the school teachers community, are incomplete and contradictory, especially in general school education. This suggests the need to improve methods of collecting statistical information in the field of public education.